GIS-BASED RISK MONITORING OF ZOONOTIC CESTODIASIS IN HUMAN - V. V. Belimenko; N. A. Samoylovskaya; E. V. Novosad; P. I. Christianovsky (Российский паразитологический журнал, 2016)
Objective of research: The target of the paper is to develop a model of GIS-based risk monitoring of zoonotic cestodiasis in human.Materials and methods: The use of geographic information systems (GIS) as an epizootiological and epidemiological method for the risk-based monitoring of human cestodiasis enables the development of a multi-level platform for solution of a wide range of tasks related to the control of this disease. The modern GIS tools use the methods of geoinformatics applying powerful software and hardware: open access geographic web servers, tools for multidimensional complex analysis, creating most accurate electronic and paper maps. Full-featured GIS contain a full set for processing geospatial data including acquisition of data, its integration and storage, automatic data processing, editing, creation and maintenance of topology, spatial analysis, access to the database management system (DBMS), visualization and creation of hard copies of any cartographic data.Results and discussion: The use of GIS enables to study more closely the regularities of epizootic process, geography of human cestodiasis and to improve the methodology both for short-term and long-term retrospective epizootiological analyses.